Abortivna tableta - Pretnar-Darovec, Alenka (Zdravniški vestnik, 2002)
Background. This contribution describes the history of the abortion pill, its introduction in the world and in our country. On the basis of the findings of the studies, carried out since the early 80s, the authors provide the indications and contraindications for the application of the method. Conclusions. The most efficient method for termination of an early pregnancy with least adverse side effects is the combination of drugs, viz. 1 tablet of mifepristone (200 mg) administered orally and 4 tablets (4 x 200 mcg) of misoprostol applied vaginally.
Keywords: Abortifacient agents; Abortivi; abortus; Administration, intravaginal; Administration, oral; ginekologija; human pregnancy; Mifepriston; Mifepristone; Misoprostol; Mizoprostol; nosečnost; tablete; Zdravilo, oralna uporaba; Zdravljenje intravaginalno